Czech Republic : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
The Czech economy has rebounded from the downturn owing to its strong fundamentals and the global recovery. Domestic demand has become self-sustaining since mid-2010. Fixed investment grew moderately in the second half of 2010, mostly on account of one-off factors. GDP has grown by 2.3 percent in 2010. Despite accommodative monetary policy, inflation pressures remained subdued until the recent surge in commodity prices. The virtually foreign-owned banking system has been stable throughout the crisis. Fiscal consolidation has commenced in 2010 and helped yield significant credibility gains.